Chaetomitrium Papillifolium - Monica Suleiman; Hiroyuki Akiyama (2014)
(1) Branches are erect or strongly incurved when dry, with filamentous propagules in leaf axils near the tips; (2) branch leaves are acuminate, slightly constricted below apices; (3) leaf margins are denticulate with geminate teeth; (4) lamina cells are linear, strongly prorate, thick-walled; (5) setae are 8 mm long, papillose above and smooth at the extreme base; (6) capsules are inclined with smooth surface; (7) calyptrae are mitriform, laxly setulose above, with long hairs below.